Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan (Studi Kasus Pada Pegawai Perumda Tirta Mangkaluku Kota Palopo) - Amanda, Amanda; Bachri, Samsul; Wahida, Altri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to evaluate the influence of financial literacy and lifestyle on the financial management behavior of employees at Perumda Tirta Mangkaluku Kota Palopo. Using a quantitative approach through surveys, data were collected randomly from employees using a questionnaire covering the three variables. The results of multiple regression analysis indicate that both financial literacy and lifestyle have a significant and positive effect on financial management behavior. These findings highlight the importance of improving financial literacy and promoting a positive lifestyle among employees, which contributes not only to their personal financial well-being but also to overall company performance. Based on these results, it is recommended that Perumda Tirta Mangkaluku Kota Palopo develop more relevant and effective financial education programs and foster a work environment that supports healthy living and prudent financial management.